125Manual vs. automatic local activation time annotation for guiding premature ventricular complex ablation procedures (MANIaC - PVC study). (18th June 2020) - Jauregui, B; Fernandez-Armenta, J; Acosta, J; Penela, D; Teres, C; Ordonez, A; Soto-Iglesias, D; Silva, E; Chauca, A; Bisbal, F; Pedrote, A; Berruezo, A
Abstract: Funding Acknowledgements: Financial support was provided in form of a research grant from Biosense Webster Introduction:  The use of an algorithmic method (wavefront, WF) based on automatic annotation of the maximal negative slope of the unipolar electrogram (uni-EGM) within the window demarcated by the bipolar EGM (bi-EGM) may accurately identify the earliest activation site (EAS) during premature ventricular complex (PVC) ablation procedures. Purpose:  To assess the potential benefits of a local activation time (LAT) automatic acquisition protocol using WF plus an automatic algorithm for ECG pattern matching recognition (AUT-arm) instead of a manual LAT annotation plus ECG visual inspection (MAN-arm) during premature ventricular complexes (PVCs) ablation procedures. Methods:  Prospective, randomized, controlled and international multicenter study (NCT03340922). 69 consecutive patients with indication for PVC ablation were enrolled and randomized to AUT (n = 34) or MAN (n = 35) annotation protocols using the CARTO3 navigation system. The primary endpoint was mapping success, defined as complete PVC abolition after a maximum of 2 radiofrequency (RF) applications or up to 90 seconds at the identified EAS, considered the site of origin (SOO). Complete PVC abolition was considered as the procedure success, whereas clinical success was defined as the PVC-burden reduction of >80% in the 24-h Holter at least 1 month after the procedure. Concordance analysis of the maps obtained with both methods was performed. Results:  Mean age was 69 ± 15, 58% men. The mean baseline PVC burden was 26 ± 13%, mean LVEF 55 ± 12%. Baseline characteristics were similar between groups. The most frequent PVC-SOO were RVOT (41%), LV (25%; being the summit the most frequent location), and LVOT (16%), with no MAN-AUT differences. Total mapping time, number of RF applications, RF time, and procedure time were similar for both groups. The AUT-arm had a higher number of mapping points acquired (164 vs. 61; p = 0.002). There was a delayed detection of LAT at the EAS in the AUT-arm (mean 23 ± 13 ms), being more significant in left-sided PVCs (30 ± 12 vs. 15 ± 9 ms, p < 0.001). The 10-ms isochronal area was significantly bigger in the MAN-arm (1.95 ± 2.7 vs. 1.0 ± 1.0; p = 0.05). The median (interquartile range) distance between AUT-EAS and MAN-EAS was 4 (0–6.8) mm. Mapping success was similar for AUT (65%) and MAN (63%) (p = 1.0). Procedure success was significantly better for the AUT-arm (100% AUT vs. 86% MAN; p = 0.04), but without differences in clinical success (87% AUT vs. 82% MAN; p = 0.7). There were no procedure-related complications. Conclusions:  The use of a complete automatic protocol for LAT annotation (WF + ECG pattern matching) during PVC ablation procedures is feasible and safe, allowing to achieve equivalent procedural and clinical endpoints as compared to manual procedures carried out by expert operators.